Dimensional tolerances for additive manufacturing: Experimental investigation for Fused Deposition Modeling - Lieneke, Tobias; Denzer, Vera; Adam, Guido; Zimmer, Detmar (CAT 2016)
Additive manufacturing creates parts in layers without using formative tools. Compared to established manufacturing processes, additive manufacturing offers many advantages. However, only a few research institutions and technology-leading companies use additive manufacturing for end-use part production because relevant challenges have not been sufficiently researched yet. Missing restrictions become apparent in the available geometrical accuracy. The objective of this investigation was the experimental determination of dimensional tolerances using standard parameters. To this end, a methodical procedure was set up. Based on experimentally determined deviations, dimensional tolerances were derived.

Effizienzorientierte Optimierung der Baustruktur von MMDS-Sammelgetrieben - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Intelligent Operating Strategy for an Internal Rubber Mixer's Multi-Motor Drive System Based on Artificial Neural Network - Strop, Malte; Zimmer, Detmar (IEEE 21st International Conference on Emerging Technologies and Factory Automation (ETFA))

Örtlich konzentrierte Mehrmotorenantriebssysteme - Ein Lösungsansatz für ganzheitlich modulare Antriebssysteme - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Optimierung von Planetengetriebemotoren - Einfluss des Übersetzungsverhältnisses auf das Kosten-, Gewichts-, Verlust-, Dynamik- und Zuverlässigkeitsverhalten von Planetengetriebemotoren - Kücükyavuz, Ali Kemal

Beitrag zur Reduzierung der Verluste von fluidabdichtenden Wellendichtsystemen - Nolte, Karsten

Verbundprojekt Energieeffiziente Federkraftbremse: Abschlussbericht. Berichtszeitraum: 01.05.2012 - 31.03.2016 - Schadomsky, Magnus Hubert; Zimmer, Detmar; Kriegel, Nils-Peter; Neumann, Christoph; Küter, Winfried; Menzel, Eckard

A Holistic and Adaptive Approach for Automated Prototyping of Image Processing Functionality - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 21st IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))
Image Processing is fundamental for any camera-based vision system. In order to automate the prototyping process of image processing solutions to some extend, we propose a holistic, adaptive approach that comprises concepts for specification, composition, recommendation, execution, and rating of image processing functionality. The fundamental idea is to realize image processing applications according to Service-oriented Computing design principles. That is, distinct image processing functionality is encapsulated in terms of stateless services. Services are then used as building blocks for more complex image processing functionality. To automatically compose complex image processing functionality, our proposed approach incorporates a flexible, Artificial Intelligence planning-based forward search algorithm. Decision-making between alternative composition steps is supported by a learning recommendation system, which keeps track of valid composition steps by automatically constructing a composition grammar. In addition, it adapts to solutions of high quality by means of feedback-based Reinforcement Learning techniques. A concrete use case serves as proof of concept and demonstrates the feasibility of our holistic, adaptive approach.

Do talented women shy away from competition? - Hoyer, Britta; van Huizen, Tomas; Keijzer, Linda; Rezai Khavas, Tahere; Rosenkranz, Stephanie
We study the willingness to compete in a cognitive task among an entire cohort of fresh man business and economics students. Combining data from a lab-in-thefield experiment with university admissions data, we trace the gender gap in competitiveness at different levels of high school performance. Our results confirm that, on average, men choose to compete more often. The gender gap disappears, however, among students with above average high school performance. Female high school top performers are equally competitive as their male counterparts. In fact, the overall gender gap is entirely driven by the group of female high school underperformers who shied away from competition, even when they performed well in our task. Overall, our findings suggest that high school grades are more than just a signal of cognitive abilities, because they seem to influence the receivers selfperception of his or her performance in a competitive environment involved in later on in life.

A Formal Approach to Error Localization and Correction in Service Compositions - Krämer, Julia; Wehrheim, Heike (Proceedings of the 1st International Workshop on Formal to Practical Software Verification and Composition (VeryComp 2016))
Error detection, localization and correction are time-intensive tasks in software development, but crucial to deliver functionally correct products. Thus, automated approaches to these tasks have been intensively studied for standard software systems. For model-based software systems, the situation is different. While error detection is still well-studied, error localization and correction is a less-studied domain. In this paper, we examine error localization and correction for models of service compositions. Based on formal definitions of error and correction in this context, we show that the classical approach of error localization and correction, i.e. first determining a set of suspicious statements and then proposing changes to these statements, is ineffective in our context. In fact, it lessens the chance to succeed in finding a correction at all.In this paper, we introduce correction proposal as a novel approach on error correction in service compositions integrating error localization and correction in one combined step. In addition, we provide an algorithm to compute such correction proposals automatically.

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces - Hajiraissi, Roozbeh; Giner, Ignacio; Grundmeier, Guido; Keller, Adrian (Langmuir)

Regular Nanoscale Protein Patterns via Directed Adsorption through Self-Assembled DNA Origami Masks - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Stewart, A. Francis; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Temperature-Dependent Charge Transport through Individually Contacted DNA Origami-Based Au Nanowires. - Teschome, B; Facsko, S; Schönherr, T; Kerbusch, J; Keller, Adrian; Erbe, A (Langmuir)

DNA annealing by Redβ is insufficient for homologous recombination and the additional requirements involve intra- and inter-molecular interactions. - Subramaniam, S; Erler, A; Fu, J; Kranz, A; Tang, J; Gopalswamy, M; Ramakrishnan, S; Keller, Adrian; Grundmeier, Guido; Müller, D; Sattler, M; Stewart, AF (Scientific Reports)

Plasma-Enhanced Chemical Vapor Deposition (PE-CVD) yields better Hydrolytical Stability of Biocompatible SiOx Thin Films on Implant Alumina Ceramics compared to Rapid Thermal Evaporation Physical Vapor Deposition (PVD) - Böke, Frederik; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido; Fischer, Horst (ACS Applied Materials & Interfaces)

Anisotropic metal growth on phospholipid nanodiscs via lipid bilayer expansion - Oertel, Jana; Keller, Adrian; Prinz, Julia; Schreiber, Benjamin; Hübner, René; Kerbusch, Jochen; Bald, Ilko; Fahmy, Karim (Scientific Reports)

Structural stability of DNA origami nanostructures in the presence of chaotropic agents - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Nanoscale)

Adsorption and adhesion studies of PdSn-nanoparticles on protonated amine and carboxylic acid-terminated surfaces - Mosebach, Bastian; Bayer, Frank Markus; Fels, Carl-Christian; Voigt, Markus; Oezkaya, Berkem; Pomorska, Agata; Torun, Boray; Keller, Adrian; Grundmeier, Guido (Surface and Interface Analysis)

A CEGAR Scheme for Information Flow Analysis - Töws, Manuel; Wehrheim, Heike (Proceedings of the 18th International Conference on Formal Engineering Methods (ICFEM 2016))
Information flow analysis studies the flow of data between program entities (e.g. variables), where the allowed flow is specified via security policies. Typical information flow analyses compute a conservative (over-)approximation of the flows in a program. Such an analysis may thus signal non-existing violations of the security policy.In this paper, we propose a new technique for inspecting the reported violations (counterexamples) for spuriousity. Similar to counterexample-guided-abstraction-refinement (CEGAR) in software verification, we use the result of this inspection to improve the next round of the analysis. We prove soundness of this scheme.

Die Rolle der Reputation: Die Entstehung, der Aufbau, die Messung und die Auswirkung der Reputation auf Kunden und Unternehmen - Hesso, Aref

Scanning Kelvin Probe Blister test measurements of adhesive delamination – Bridging the gap between experiment and theory - Grothe, R.; Liu, Chen-Ni; Baumert, M.; Hesebeck, O.; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Influence of O2 exposure on the interaction between CH4 and amorphous AlYB14 - Hunold, Oliver; Wiesing, Martin; de los Arcos, Teresa; Music, Denis; Grundmeier, Guido; Schneider, Jochen M. (Applied Surface Science)

In situPM-IRRAS studies of organothiols and organosilane monolayers-ZnO interfaces at high water activities - Torun, Boray; Giner, Ignacio; Grundmeier, Guido; Ozcan, Ozlem (Surface and Interface Analysis)

Influence of stripping and cooling atmospheres on surface properties and corrosion of zinc galvanizing coatings - Yasakau, K.A.; Giner, I.; Vree, C.; Ozcan, O.; Grothe, R.; Oliveira, A.; Grundmeier, Guido; Ferreira, M.G.S.; Zheludkevich, M.L. (Applied Surface Science)

Effect of Pre-Rolling Heat Treatments on the Bond Strength of Cladded Galvanized Steels in a Cold Roll Bonding Process - Hordych, Illia; Rodman, Dmytro; Nürnberger, Florian; Hoppe, Christian; Schmidt, Hans Christian; Grundmeier, Guido; Homberg, Werner; Maier, Hans Jürgen (steel research international)

Ageing mechanisms of polyurethane adhesive/steel interfaces - Weiss, J.; Voigt, M.; Kunze, C.; Sánchez, J.E. Huacuja; Possart, W.; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Adhesion and corrosive delamination of epoxy films on chemically etched ZnMgAl-alloy coatings - Pohl, K.; Ozcan, O.; Voigt, M.; Grundmeier, Guido (Materials and Corrosion)

Cold pressure welding by incremental rolling: Deformation zone analysis - Schmidt, Hans Christian; Homberg, Werner; Hoppe, Christian; Grundmeier, Guido; Hordych, Illia; Maier, Hans Jürgen

Einsatz- und Nutzenpotentiale von Augmented Reality im Kontext von Industrie 4.0 - Röltgen, Daniel; Anacker, Harald; Dumitrescu, Roman (VDE Kongress 2016 Internet of Things, Mannheim, Deutschland, 7. - 8. Nov. 2016)

Einsatz von Leuchten zur Standortbestimmung in der Produktion - Falkowski, Tommy; Fechtelpeter, Christian; Peitz, Christoph; Kühn, Arno; Dumitrescu, Roman (VDE Kongress 2016, 7. - 8. Nov. 2016)

Reference Architecture and Maturity Levels for Cyber-Physical Systems - Westermann, Matthias; Anacker, Harald; Dumitrescu, Roman; Czaja, Anja Maria (2nd IEEE International Symposium on Systems Engineering 2016, Edinburgh, Scotland, 4. - 5. Okt. 2016)

Reliability in MID - barriers, potentials, fields of action - Fechtelpeter, Christian; Jürgenhake, Christoph; Dumitrescu, Roman; Mager, Thomas; Fritz, Karl-Peter; Grötzinger, Tobias; Müller, Hagen; Wild, Paul; Zimmermann, Andre (12th International Congress on Molded Interconnect Devices, Conference Proceedings , 28. - 30. Sep. 2016)

Classification of MID-prototypes - Jürgenhake, Christoph; Falkowski, Tommy; Dumitrescu, Roman (12th International Congress on Molded Interconnect Devices, Würzburg, 28. - 30. Sep. 2016)

Value Network Design for Innovations: Developing Alternative Value Network Drafts - Kage, Martin; Drewel, Marvin; Gausemeier, Jürgen; Schneider, Marcel (Technology Innovation Management Review)

Systematic for function-oriented development of spatial integrated circuit carriers - Jürgenhake, Christoph; Dumitrescu, Roman (International Design Conference - Design 2016, 16. - 19. Mai 2016)

Value Network Design for Innovations - Kage, Martin; Drewel, Marvin; Gausemeier, Jürgen; Schneider, Marcel (Proceedings of the 5th ISPIM Innovation Forum)

Exhaustiveness of Systems Structures in Model-Based Systems Engineering for Mechatronic Systems - Kaiser, Lydia; Bremer, Christian; Dumitrescu, Roman (Sysint - 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)

Function-based feasibility study and benchmark for MID concepts - Jürgenhake, Christoph; Falkowski, Tommy; Fechtelpeter, Christian; Dumitrescu, Roman (Sysint - 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)

A concept for managing information in early stages of product engineering by integrating MBSE and workflow management systems - Bretz, Lukas Helmut; Tschirner, Christian; Dumitrescu, Roman (IEEE ISSE: Proceedings of 2016 International Symposium on Systems Engineering)

Additive Fertigung - Gausemeier, Jürgen; Schmidt, Michael; Anderl, Reiner; Schmid, Hans-Joachim; Leyens, Christoph; Seliger, Günther; Karg, Michael; Kage, Martin

Indirect Force Control in Hardware-in-the-Loop Simulations for a Vehicle Axle Test Rig - Olma, Simon; Kohlstedt, Andreas; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (14th International Conference on Control, Automation Robotics & Vision (ICARCV))

Feature Model Based Interface Design for Development of Mechatronic Systems

PROFINET-Implementierung im Rahmen der Entwicklung eines intelligenten, selbstlernenden Teigkneters - Holtkötter, Jens; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Oestersötebier, Felix; Wessels, Sebastian (Virtuelle Instrumente in der Praxis 2016)

A HRRN based scheduling for FMS and RMS with networked control and product-intelligence - Bertelsmeier, Fabian; Pollmann, Jan; Trächtler, Ansgar (Inproceedings of the IEEE IECON 2016)

Model Predictive Feedforward Compensation for Control of Multi Axes Hybrid Kinematics on PLC - Rüting, Arne Thorsten; Blumenthal, Lars Martin; Trächtler, Ansgar (Proceedings of IEEE IECON 2016)

Nichtlineare Zustandsregelung mit Sliding-Mode-Beobachter für einen Achsprüfstand mit hydraulischem Hexapoden - Olma, Simon; Traphöner, Phillip; Kohlstedt, Andreas; Trächtler, Ansgar (GMA Fachausschuss 1.40 "Theoretische Verfahren der Regelungstechnik")

Substructuring and Control Strategies for Hardware-in-the-Loop Simulations of Multiaxial Suspension Test Rigs - Olma, Simon; Kohlstedt, Andreas; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 7th IFAC Symposium on Mechatronic Systems)

Study of a rail-bound parallel robot concept with curvilinear closed-path tracks - Bielawny, Dirk; Wang, Peng; Trächtler, Ansgar (Proceedings of 7th IFAC Symposium on Mechatronic Systems & 15th Mechatronics Forum International Conference)

Multiobjective Model Predictive Control of an Industrial Laundry - Peitz, Sebastian; Graeler, Manuel; Henke, Christian; Hessel-von Molo, Mirko; Dellnitz, Michael; Trächtler, Ansgar (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Design and Implementation of Intelligent Control Software for a Dough Kneader - Oestersötebier, Felix; Traphöner, Phillip; Reinhart, Felix; Wessels, Sebastian; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Approach for an Integrated Model-Based System Design of Intelligent Dynamic Systems Using Solution and System Knowledge - Oestersötebier, Felix; Abrishamchian, Farisoroosh; Lankeit, Christopher; Just, Viktor; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Model-based method for the accuracy analysis of Hardware-in-the-Loop test rigs for mechatronic vehicle axles - Olma, Simon; Traphöner, Phillip; Kohlstedt, Andreas; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Disturbance Observer Design for Utilizing of Time-delayed Vision Measurements in High Dynamic Systems - Wang, Shuo; Just, Viktor; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Development and design of intelligent product carriers for ﬂexible networked control of distributed manufacturing processes - Bertelsmeier, Fabian; Schöne, Stefan; Trächtler, Ansgar (Inproceedings of the IEEE 24th Mediterranean Confernce on Control and Automation (MED))

Control of a hydraulic hexapod for a Hardware-in-the-Loop axle test rig - Kohlstedt, Andreas; Olma, Simon; Flottmeier, Sarah; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (at-Automatisierungstechnik)

Consistency Analysis for Requirements, Functions, and System Elements - Lankeit, Christopher; Just, Viktor; Trächtler, Ansgar (IEEE Systems Conference)

Product Data and Sensor-based Intelligent Drive Control for Flexible Manufacturing and Intralogistic Processes - Geneiß, Volker; Hedayat, Christian; Bertelsmeier, Fabian; Henke, Christian; Vathauer, Karl-Ernst; Geßner, Thomas (Inproceedings of Smart Systems Integration 2016 International Conference and Exhibition on integration of materials, devices and systems)

Modellbildung und Simulation im Kontext des Systems Engineering - Michael, Jan; Holtkötter, Jens; Henke, Christian; Trächtler, Ansgar (ASIM-Treffen STS/GMMS 2016)

Implementing intelligent technical systems into smart homes by using model based systems engineering and multi-agent systems - Michael, Jan; Hillebrand, Michael; Wohlers, Benedict; Henke, Christian; Dumitrescu, Roman; Trächtler, Ansgar (Renewable Energy and Power Quality Journal (RE&PQJ) 16)

Precision Control of SMA Actuators with a Real Time Model-Based Controller and Extended VSC - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IFAC-PapersOnLine)

Regelungstechnik - Föllinger, Otto; Konigorski, Ulrich; Lohmann, Boris; Roppenecker, Günter; Trächtler, Ansgar

A model extended temperature and strain controller modulated with PWM for precision position control of shape memory alloy actuators - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IEEE International Conference on Advanced Intelligent Mechatronics AIM)

Multidomänenmodell zur Optimierung der Hydraulik eines Raupenlaufwerks für Landmaschinen - Kruse, Daniel; Warkentin, Andreas P.; Krüger, Martin; Trächtler, Ansgar; Rackow, Sascha (Proc. 4. Internationales Commercial Vehicle Technology Symposium)

Consensus-based local information coordination for the networked control of the autonomous intersection management - Wuthishuwong, Chairit; Trächtler, Ansgar (Complex & Intelligent Systems)

Simultaneous path planning and trajectory optimization for robotic manipulators using discrete mechanics and optimal control - Shareef, Zeeshan; Trächtler, Ansgar (Robotica)

Verbesserte Schätzung von Fahrdynamikgrößen durch Modellierung der Fahrwerks-und Lenkkinematik - Renninger, Johannes; Trächtler, Ansgar (at-Automatisierungstechnik)

A Tool Chain for Model-Based Development of Heat Pump Dryers - Bockholt, Marcos; Katter, Michael; Pohl, Georg; Michael, Jan; Alpögger, Thomas (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Supporting the Decision Process for applying Additive Manufacturing in the MRO Aerospace Business by MADM - Deppe, G.; Koch, R. (27th Annual International Solid Freeform Fabrication Symposium)
The spare part industry in aerospace is highly demanding. For conventional manufacturing technologies it is difficult to meet these requirements. In contrast to that, the design freedom of Additive Manufacturing enables the production of complex and lightweight parts. The lack of experience with this technology hampers the decision where Additive Manufacturing can be economically applied. The cost drivers have to be newly evaluated and holistically investigated. Supply chain advantages have to be considered during the decision process, too. Therefore, aerospace characteristics are analyzed within the paper and a methodology based on Multi Attribute Decision Making (MADM) is introduced. To do so, the cost appraisal for Additive Manufacturing has to be detailed. Additionally, changes in the supply chain have to be identified and quantified. Quality criteria have to be taken into account as well. In the end it is shown how these influence factors can be combined to create a decision support.

Product optimization with and for Additive Manufacturing - Reiher, T.; Koch, R. (27th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing offers a great potential for the optimization of products. Therefore different approaches are feasible to exploit these potentials for elaborating optimal solutions. For example these include optimization of weight or stiffness of structural components as well as the integration of functions and other entities of assemblies. Note, however, that additive manufacturing processes have process specific limitations. Products, components and assemblies, as well as procedures for the design and production preparation must be optimized with regard to a successful additive manufacturing. The use of already known tools for the optimization and design needs to be reconsidered and adapted to theadditive manufacturing. This also includes the production planning with component orientation in build chamber as well as a necessary quality management system. This paper shows several ways for product optimization with additive manufacturing, often based on topology optimization, and procedures for information gathering, decision making and shape determination for part optimization for Additive Manufacturing.

Cost Efficient Design and Planning for Additive Manufacturing Technologies - Lindemann, C.; Koch, R. (27th Annual International Solid Freeform Fabrication Symposium)
Additive manufacturing offers advantages for the production of a final product. Nowadays still many companies have not integrated this new technology into their product development processes (PDP). This paper will discuss additive manufacturing with regards to the current available PDP's while setting a focus on the economic aspects of the integration. Based on a sample part several tools will be discusses which may be uses in the different phases of product development. These tools aim on the simplification of integrating additive manufacturing technologies into existing PDP's. Included are methods for early and accurate cost estimation as well as product selection processes, best practice templates for creating knowledge and process awareness.

Scenario Based Outlook of Additive Manufacturing Applications for the Aerospace Market - Lindemann, C.; Deppe, G.; Koch, R.
Additive Manufacturing (AM) has been growing rapidly with doubledigit growth rates during the last years and a rising trend towards end products. The further development of the technology highly depends on some critical success factors. For the future, it is vital to know which innovations will be necessary to satisfy the needs of industry. The impulsive forces will be those branches whose special characteristics are met by AM. Within the DMRC study “Thinking ahead the Future of Additive Manufacturing – Analysis of Promising Industries” (Gausemeier 2011), especially aircraft production, automotive production and the electronics industry have been identified as very promising to profit from the use of AM. Experts have selected these branches by assessing the prospective attractiveness of current application fields. Those branches are characterized by low quantities, complex part designs, lightweight design and/or high unit prices. For the aerospace industry, all four elements are of high relevance, which is why it has been a pioneer in applying and developing AM technology since the early beginning (Gausemeier 2011 and 2012).

Prevention of Product Piracy - Potentials of Additive Manufacturing - Jahnke, U.; Koch, R.
Additive Manufacturing (AM) is often deemed to be a driver for product piracy in public media. The reasons for this are mainly seen in the fact that it provides a possibility to easily copy three-dimensional objects when used in combination with scanning technologies. This contribution will not focus on the knowledge and skills needed to master AM technology but on its potential contribution to prevent product piracy and reverse engineering. The reverse engineering process will be analyzed to understand the practice of imitators and to transfer the characteristics of AM into specific measures. Finally a five-step methodology is presented which can be used as a guideline to implement protection measures in products to be (re-) developed. This guideline is supposed to be used by industrial companies since an expert survey has identified them as being very likely to profit from the use of AM (Echterhoff et al. 2011).

Automatized Derivation of Comprehensive Specifications for Black-box Services - Schwichtenberg, Simon (Proceedings of the 38th International Conference on Software Engineering Companion (ICSE))
Today, cloud vendors host third party black-box services, whose developers usually provide only textual descriptions or purely syntactical interface specifications. Cloud vendors that give substantial support to other third party developers to integrate hosted services into new software solutions would have a unique selling feature over their competitors. However, to reliably determine if a service is reusable, comprehensive service specifications are needed. Characteristic for comprehensive in contrast to syntactical specifications are the formalization of ontological and behavioral semantics, homogeneity according to a global ontology, and a service grounding that links the abstract service description and its technical realization. Homogeneous, semantical specifications enable to reliably identify reusable services, whereas the service grounding is needed for the technical service integration. In general, comprehensive specifications are not availableand have to be derived. Existing automatized approaches are restricted to certain characteristics of comprehensiveness. In my PhD, I consider an automatized approach to derive fully-fledged comprehensive specifications for black-box services. Ontological semantics are derived from syntactical interface specifications. Behavioral semantics are mined from call logs that cloud vendors create to monitor the hosted services. The specifications are harmonized over a global ontology. The service grounding is established using traceability information. The approach enables third party developers to compose services into complex systems and creates new sales channels for cloud and service providers.

Combining material efficiency and part reliability by product optimization applying additive manufacturing - Reiher, T.; Deppe, G.; Koch, R. (International Conference Production Engineering and Management 2016)
Nowadays, the material efficiency and part reliability are two majorissues in product development. Thus a product optimization often requires complex structures that are hard to be manufactured conventionally. Additive Manufacturing (AM) however offers great potentials for producing complex shaped parts economically. Different approaches are feasible to exploit these potentials based on the part’s application from shape optimization of structural components to the integration of functions and other entities of assemblies. Several parameters are defined that influence the costs and quality of the future product and carefully have to be balanced. To do so, the use of already known tools for the optimization and design needs to be reconsidered and adapted to the special characteristics of AM. As not all optimization potentials can be realized perfectly, a decision methodology is required to obtain the relevant potentials and to get to a trade-off between all requirements including the ecological impact. The paper shows different approaches for product optimization with AM and procedures for decision making in order to get to the optimal solution.

Unterstützung des AM Entscheidungsprozesses in der Luftfahrtersatzteilversorgung - Deppe, G.; Koch, R. (Rapid Tech 2016)
Additive Fertigungsverfahren bieten in der Luftfahrtindustrie großes Potential. Die Geometriefreiheit ermöglicht die Produktion von komplexen und gewichtsoptimierten Bauteilen. Die mangelnde Erfahrung der Unternehmen mit dieser Fertigungstechnologie erschwert jedoch die Entscheidung, an welcher Stelle Additive Manufacturing ökonomisch sinnvoll eingesetzt werden kann. Die Kosteneinflussfaktoren unterscheiden sich an vielen Stellen von denen traditioneller Fertigungsverfahren und müssen gänzlich neu bewertet und eingeordnet werden. Dabei verlagert sich auch der Fokus weg von den reinen Herstellkosten hinzu einer ganzheitlichen Kostenbetrachtung. Wesentliche Vorteile lassen sich auch meist in der Supply Chain erzielen und müssen im Zuge des Entscheidungsprozesses für ein Fertigungsverfahren bei einem bestimmten Bauteil berücksichtigt werden. Daher werden in der Präsentation die Charakteristika der Luftfahrt analysiert und die Methodik einer Entscheidungsunterstützung vorgestellt. Im Zuge dessen gilt es die Kostenbewertung additiver Fertigungsverfahren näher zu beleuchten, um die Fertigungs- bzw. Reperaturkosten mit traditionellen Verfahren vergleichen zu können. Weiterhin müssen Veränderungen in der Supply Chain identifiziert und bewertbar gemacht werden. Qualitätskriterien müssen ebenfalls mit in die Betrachtung einbezogen werden. Anschließend wird aufgeziegt wie diese Einflussfaktoren in die Entscheidungsunterstützung integriert sind.

Adding atmospheric scattering and transparency to a deferred rendering pipeline for camera based ADAS tests - Heppner, Sabrina; Dransfeld, Marius; Domik, Gitta (Informatik 2016)

A Deferred Rendering Pipeline Including a Global Illumination Model for Atmospheric Scattering and Transparency - Heppner, S.; Dransfeld, M.; Domik, Gitta (Vision, Modeling & Visualization)

3D Image Display Courses for Information Media Students - Yanaka, K.; Yamanouchi, T. (IEEE Computer Graphics and Applications)

Using Heuristic Evaluation to Foster Visualization Analysis and Design Skills - Santos, B. S.; Ferreira, B. Q.; Dias, P. (IEEE Computer Graphics and Applications)

Automatic Composition of Service-based Image Processing Applications - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 13th IEEE International Conference on Services Computing (SCC))
In the Image Processing domain, automated generation of complex Image Processing functionality is highly desirable; e.g., for rapid prototyping. Service composition techniques, in turn, facilitate automated generation of complex functionality based on building blocks in terms of services. For that reason, we aim for transferring the Service Composition paradigm into the Image Processing domain. In this paper, we present our symbolic composition approach that enables us to automatically generate Image Processing applications. Functionality of Image Processing services is described by means of a variant of first-order logic, which grounds on domain knowledge operationalized in terms of ontologies. A Petri-net formalism serves as basis for modeling data-flow of services and composed services. A planning-based composition algorithm automatically composes complex data-flow for a required functionality. A brief evaluation serves as proof of concept.

Architectural Management of On-The-Fly Computing Markets - Jazayeri, Bahar (Proceedings of the 10th European Conference on Software Architecture (ECSA Workshops))
Existing software markets like Google Play allow users to search among available Apps and select one based on the description provided for the App or based on its rating. Future software markets facilitate on-the-fly composition of such Apps based on users’ individual wishes. Realizing such On-The-Fly Computing (OTF) markets requires support of sophisticated software features. In addition, suitable orchestration among such features needs to ensure well-alignment of business and IT aspects in case of run-time changes like market dynamics. However, all these introduce new architectural and management complexities, which are specific to such markets. An architecture framework for OTF markets will include design solutions to overcome these complexities. In my PhD, I aim at identifying an architecture framework for OTF markets including main architectural building blocks and a systematic development process. Such an architecture framework enables the development of OTF markets in the future. Furthermore, this knowledge can be used as a basis to improve existing software markets by integrating missing functionalities.

Evaluating bilingual education in Germany: CLIL students’ general English proficiency, EFL self-concept and interest - Rumlich, Dominik
Reviews/Rezensionen: Lasagabaster (2017) in der Zeitschrift Journal of Immersion and Content-Based Language Education, 5(1) :https://www.jbe-platform.com/content/journals/10.1075/jicb.5.1.06las] Burmeister (2019) in der Zeitschrift Fremdsprachen Lehren und Lernen, 48(1): http://www.periodicals.narr.de/index.php/flul/article/view/4836 Breeze (2018) in der Zeitschrift Estudios sobre Educación, 34(1): https://www.unav.edu/publicaciones/revistas/index.php/estudios-sobre-educacion/article/download/21762/17478

Variational tensor approach for approximating the rare-event kinetics of macromolecular systems - Nüske, Feliks; Schneider, Reinhold; Vitalini, Francesca; Noé, Frank (The Journal of Chemical Physics)

Data Management for additive manufacturing: survey on requirements and current state - Gräßler, I.; Taplick, P.; Pottebaum, J.; Scholle, P.; Reiher, T. (14th International DESIGN Conference 2016)
The paper gives an overview of actually used Additive Manufacturing (AM) data formats and AM data infrastructure. Based on empirical analysis of the actual situation, necessary improvement of data management and exchange formats in context with AM technology is derived. The purpose of this paper is to understand the actual use of data formats and management in the field of AM. The paper draws conclusions based on an empirical analysis of the used data formats dependent on stakeholder groups. The results of the expert survey show a necessity to improve or develop new AM specific data formats.

Application Deployment at Distributed Clouds - Keller, Matthias

Fatigue Behavior of FDM Parts Manufactured with Ultem 9085 - Fischer, M.; Schöppner, Volker (27th Annual International Solid Freeform Fabrication Symposium)
The mechanical characterization of fused deposition modeling (FDM) parts is mostly done by static tests. In many applications, parts are also dynamically loaded. Here, fatigue tests can help to identify the expected lifetime of a part. This article discusses the fatigue behavior of FDM specimens manufactured with Ultem 9085. For this, tensile bars are manufactured according to ASTM D638 in different build orientations. Tests are performed in a range of pulsating tensile stresses, and S-N curves are documented for different build orientations. For higher loads, the FDM anisotropy characterizes the lifetime of used specimens, which is similar to static tensile bars. For lower loads, including a higher number of cycles to failure, S-N curves of different build orientations converge. In further tests, tensile bars were chemically smoothed with chloroform vapor. Chemical smoothing reduces surface roughness and increases tensile strength of specimens in the upright build direction. Fatigue tests of chemically treated specimens show no significant lifetime increase.

Universelle Mikrobearbeitungsplaffform und Basistechnologien für das Fertigen und Markieren mikrophysiologischer Systeme - Moritzer, Elmar; Hirsch, André; Günther, K.; Teutoburg-Weiss, S.; Lasagni, A.F.; Klotzbach, U.; Sonntag, F. (6. Dresdner Medizintechnik-Symposium, Biomedizinische Technik - interdisziplinär, integrativ und innovativ)
Das Fraunhofer-Institut für Werkstoff- und Strahltechnik IWS etablierte in enger Kooperation mit Partnern in den letzten Jahren erfolgreich eine geschlossene Technologiekette zur Umsetzung maßgeschneiderter mikrophysiologischer Systeme. Darauf aufbauend wurde eine universelle Mikrobearbeitungsplattform zum automatisierten Fertigen konzipiert und entwickelt. Dies umfasst neue Technologien für Schlüsselprozesse wie das Herstellen mikrofluidischer Komponenten mittels ARBURG Kunststoff-Freiformen sowie das Erzeugen funktionaler Strukturen und das Einbringen von Produktschutzmerkmalen auf innenliegenden Polymergrenzflächen mittels Direktem Laserinterferenz-Verfahren.

Chemical Surface Treatment of Ultem 9085 Parts - Fischer, M.; Seewald, O.; Schöppner, Volker (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)
The material Ultem 9085 is a flame-retardant thermoplastic polymer, which can be processed with Fused Deposition Modeling (FDM). Due to ist high strength-to-weight ratio and FST rating, Ultem 9085 parts are used in aviation. Process related staircase effects on rounded and slanting part areas require a surface treatment for end use parts. These processes include smoothing by mass finishing or coating in order to reduce surface roughness. An alternative smoothing technique is chemical surface treatment, such as the use of Acetone for ABS materials. In this paper, the surface of Ultem 9085 parts is treated with Chloroform vapor in order to solve material at the surface and smooth it. Therefore, specimens built in different build orientations are treated and tested with regard to surface roughness values and mechancial strength properties. The analysis of surface roughness and treatment time shows a significantly higher efficiency for chemical treatment in comparison to mass finishing. By employing chemical treatment, it is possible to reduce surface roughness by more than 80 % to Rz values of approximately 15 µm. Mechanical tests and measurements of the Melt Volume Rate (MVR) show no material destruction for chemical surface treatment at room temperature for less than 150 min.

The Importance of OER in European Education - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

The EU-StORe Project - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

The OER Quality Standards - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

Insights in the OER Rating – Database – Structures, Advantages and Challanges - Beutner, Marc; Duse, C; Pechuel, R; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

Use and Implementation of OERs in Germany - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

Evaluation Results concerning OER and the EU-StORe Project - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project

Innovative Ansätze zum Serious Mobile Learning für Aus- und Weiterbildung

Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEL project

Innovatives Micro-Learning im Handwerk – Konzeption auf Basis der Struktur der OPALESCE Learning Units sowie handwerksbezogene Umsetzungsbeispiele aus dem Bereich Rechnungswesen - Beutner, Marc

SEEL – Expertenhandbuch. SEEL – Handbook for experts - Beutner, Marc; Schneider, J

Optical Transitions between Confined and Unconfined States in p-Type Asymmetric GaAs/InGaAs/AlGaAs QW Structures - Sitarek, P.; Ryczko, K.; Misiewicz, J.; Reuter, Dirk; Wieck, A. (Acta Physica Polonica A)